Ermida de Nossa Senhora do Monte da Quinta de Penha Verde - Débora Marta Silva Moreira (2010)
The N. S. do Monte chapel, a cinquecentist construction established by the celebrated warrior, scientist and vice-king of India, D. João de Castro, is placed in Sintra, in Penha Verde estate. Its localization is by itself pertinent, being Sintra, a place of cultural tolerance and great syncretism, not only at the arts level but also at the level of traditions and myths that were being crossed in this "promontory of the Moon". Thus, involved in a cultural environment of unique and exclusive characteristics, and without forgetting the role of its mentor, this chapel, as well as the D. João de Castro estate where it is inserted, will be a Renaissance reference, presenting in its characteristics the large area of interests of its founder. Therefore, the arcadian scenario of the Penha Verde estate, along with the classic suggestions of the N.S. do Monte chapel, gives evidences its mentor humanism. On the other hand, on the chapel3;s sacred enclosure, the juxtaposition of classic parts with exotic elements that came from the East, being more than just a vision from D. João de Castro on the different artistic forms, manifests a consideration for such exotic objects, in a different classic antique approach. The military architecture, one other valued subject to D. João de Castro, also acquires expression in the implantation and volumetrics of the N.S. do Monte chapel, which is resembled to a fortified tower, while the morphology and the geometric project of this architectonic piece, especially in the treatment of the openings, will look to reproduce the cosmographics and astronomical concepts of its delegate, as an adhesive subject of all the constituents of the sacred enclosure of this chapel. All these areas of interest will be crossed, not only in the personality of Castro, but they will be also reproduced in the N.S. do Monte chapel, using architecture as a common platform.